2011
DOI: 10.1021/jf201255b
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Mushrooms: Comparison of the Composition of Button Mushrooms (Agaricus bisporus) Treated Postharvest with UVB Light or Sunlight

Abstract: This study compared the compositional changes in mushrooms exposed to sunlight with those occurring after commercial ultraviolet (UV) light processing. Button mushrooms (75 kg) were processed in the presence or absence of UVB light; a third group was exposed to direct sunlight. Mushroom composition was evaluated using chemical analyses. Vitamin D concentrations were 5, 410, and 374 μg/100 g (dw) in control, UVB, and sunlight groups, respectively. On a dry weight basis, no significant changes in vitamin C, fola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
66
4
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(91 citation statements)
references
References 23 publications
7
66
4
2
Order By: Relevance
“…Comparing mushrooms processed in the presence or absence of UV-B irradiation, there were only slight differences among the contents of those components from each group. These results are in accordance with a previous study ( Simon et al, 2011), which reported that no other nutritionally significant changes in mushrooms were identified under UV irradiate condition. However, extensive research is still required to evaluate the safety and toxicity of the UV-B irradiated mushroom powder in vitro study.…”
Section: )supporting
confidence: 93%
See 1 more Smart Citation
“…Comparing mushrooms processed in the presence or absence of UV-B irradiation, there were only slight differences among the contents of those components from each group. These results are in accordance with a previous study ( Simon et al, 2011), which reported that no other nutritionally significant changes in mushrooms were identified under UV irradiate condition. However, extensive research is still required to evaluate the safety and toxicity of the UV-B irradiated mushroom powder in vitro study.…”
Section: )supporting
confidence: 93%
“…These studies indicated that UV-B is more efficient than other UV sources for vitamin D 2 synthesis. In addition, exposure to UV-B irradiation produces no other nutritionally or toxicologically significant changes in mushroom composition (Simon et al, 2011). As a result, UV-B was chosen as the source for determining the optimum conditions for vitamin D 2 synthesis in shitake mushrooms.…”
mentioning
confidence: 99%
“…A review of the safety assessment and a meta-analysis of randomised controlled trials confirmed that UV light-exposed mushrooms are safe and able to improve the vitamin D status in adults presenting low baseline status [3,4]. Other published studies reported no significant changes in water-soluble vitamins, amino acids and fatty acids after the UV-B processing of mushrooms [5,6].…”
Section: Introductionmentioning
confidence: 92%
“…Kristensen et al [10] investigated the effect of a single sun exposure duration on the vitamin D 2 content of whole button mushrooms. Simon et al compared changes in key nutritional and non-nutritional analytes in whole button mushrooms exposed to solar versus artificial UV irradiation [6]. A total of five replicate samples were exposed for 150 min to the sun on three different days, unfortunately without measuring the UV-B doses.…”
Section: Introductionmentioning
confidence: 99%
“…The concentration of ergosterol was confirmed to be different depending on the type of fungus [15,51]. However, other factors are also able to determine the ergosterol content, e.g., growing and storage temperature and UV light, which can transform sterol into vitamin D [15,51,52].…”
Section: Organic Acid Profilementioning
confidence: 97%